Present-biased preferences and credit card borrowing - Stephan Meier; Charles D. Sprenger (Institute for the Study of Labor (IZA), 2009)
Some individuals borrow extensively on their credit cards. This paper tests whether present-biased time preferences correlate with credit card borrowing. In a field study, we elicit individual time preferences with incentivized choice experiments, and match resulting time preference measures to individual credit reports and annual tax returns. The results indicate that present-biased individuals are more likely to have credit card debt, and have significantly higher amounts of credit card debt, controlling for disposable income, other socio-demographics, and credit constraints.
urn:nbn:de:101:1-20090615131
Keywords: D12; D14; D91; C93; 330; Time preferences; dynamic inconsistency; credit card borrowing; field experiment; Private Verschuldung; Kreditkarte; Konsumentenverhalten; Zeitpräferenz; USA